2017
DOI: 10.1111/ijag.12334
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Zn0.5Ti0.5NbO4 microwave dielectric ceramics with Li2O‐B2O3‐SiO2 glass for LTCC application

Abstract: Single phase of dense ixiolite structure Zn0.5Ti0.5NbO4 (ZTN) microwave dielectric ceramics were synthesized at low temperature (850°C‐900°C) via solid state reaction with small amount of Li2O‐B2O3‐SiO2 (LBS) glass. There is a liquid phase generated by LBS at about 760°C, which significantly enhances the shrinkage and decreases the activation energy. And with the assistance of liquid phase, single phase of ZTN with orthorhombic structure is detected, sintering temperature of ceramics drops from 1125°C to 850°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 31 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…For instance, the choice of boric acid as a raw material instead of boron oxide is attributed to its better solubility and dispersion in deionized water when preparing Li 2 O-B 2 O 3 -SiO 2 glass frit. 24 A sol-gel method realizes better uniformity at the molecular level than a solid-state process, which is beneficial for improving the Q × f value. 25 A high sintering temperature positively affects the cation ordering of Ba(Mg 1/3 Ta 2/3 )O 3 ceramics and then improves the Q × f value.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the choice of boric acid as a raw material instead of boron oxide is attributed to its better solubility and dispersion in deionized water when preparing Li 2 O-B 2 O 3 -SiO 2 glass frit. 24 A sol-gel method realizes better uniformity at the molecular level than a solid-state process, which is beneficial for improving the Q × f value. 25 A high sintering temperature positively affects the cation ordering of Ba(Mg 1/3 Ta 2/3 )O 3 ceramics and then improves the Q × f value.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the generation of celsian crystals was closely related to the sintering temperature and liquidphase content in the ceramsite. The generation of adequate liquid-phase production could reduce the activation energy for ion diffusion, immerse the internal fine particles of the ceramsite, enhance capillary forces between particles, promote liquid flow between pores, induce sliding, rotation, re-arrangement of the internal fine particles, and accelerate solid-solid and solid-liquid reactions, thereby promoting crystal formation (Yoon et al, 2003;Shih and Jean, 2017;Yang et al, 2018). From the XRD spectra, it could be observed that as the sintering temperature increased from 1080 °C to 1140 °C, the diffraction peak intensity of celsian first increased and then decreased, reaching the maximum intensity at 1100 °C, indicating that a suitable liquid-phase content for foaming and sintering reactions could be achieved at this sintering temperature.…”
Section: Phase Analysismentioning
confidence: 99%
“…Frontiers in Materials frontiersin.org 2009; Yang et al, 2018). According to the EDS result (I), it was deduced that unreacted hematite (Fe 2 O 3 ) mainly existed in the form of particles.…”
Section: Figurementioning
confidence: 99%
“…However, adding sintering additives tends to deteriorate microwave dielectric properties, especially for the Qf value. Adopting the chemical synthesis method and using nanopowders inevitably increase cost and process complexity, which is unsuitable for industrialization production 12‐15 . Therefore, the exploration for inherently low‐firing microwave dielectric ceramics is still of great importance.…”
Section: Introductionmentioning
confidence: 99%